2013
DOI: 10.1111/apt.12232
|View full text |Cite
|
Sign up to set email alerts
|

Randomised clinical trial: vancomycin or metronidazole in patients with primary sclerosing cholangitis ‐ a pilot study

Abstract: SUMMARY BackgroundEmerging data suggest that oral antibiotics may have therapeutic effects in primary sclerosing cholangitis (PSC), but published studies are limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
182
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(189 citation statements)
references
References 46 publications
4
182
0
3
Order By: Relevance
“…Evidence of improved ALP levels in PSC patients treated with low dose vancomycin (21), as well as a case of PSC in a patient status post liver transplantation with resolution after administration of vancomycin (30), it suggests that fecal transplantation may have a role in alleviating chronic inflammation in PSC. Probiotics may also have a role in PSC, however, studies demonstrate discordant results, perhaps due to a variety of treatment durations and multiple options of probiotic compositions (31).…”
Section: Fecal Transplantation and Other Disease States With Hepatic mentioning
confidence: 98%
See 1 more Smart Citation
“…Evidence of improved ALP levels in PSC patients treated with low dose vancomycin (21), as well as a case of PSC in a patient status post liver transplantation with resolution after administration of vancomycin (30), it suggests that fecal transplantation may have a role in alleviating chronic inflammation in PSC. Probiotics may also have a role in PSC, however, studies demonstrate discordant results, perhaps due to a variety of treatment durations and multiple options of probiotic compositions (31).…”
Section: Fecal Transplantation and Other Disease States With Hepatic mentioning
confidence: 98%
“…It has been postulated that chronic cholangitis secondary to endotoxin production or inflammatory response to microbial metabolites may lead to development of PSC (19)(20)(21). Generally, alterations in microbial diversity or altered microbial metabolism is thought to produce an aberrant cholangiocyte response, either in terms of inflammation or apoptosis, and/or affecting the cholangiocyte's ability to respond appropriately to injury over time, potentially resulting in chronic liver disease (4,6,21). Biomolecules such as lipopolysaccharide, lipoteichoic acid and bacterial DNA fragments have been detected in bile, cholangiocytes and portal tracts of patients with chronic cholestatic liver disease (4,5,19).…”
Section: Microbiome Alterations In Primary Sclerosismentioning
confidence: 99%
“…Cholangitis and sepsis can occur in 3% to 23% of the cases after ERC (216,223) , particularly in those subjects with risk factors such as biliary obstruction and inadequate drainage of the biliary tree after ERC (223) . Use of prophylactic antibiotics before or durimg ERC is controversial, but several studies have reported a decrease in infectious complications in patients under antibiotic coverage (224) , particularly in the presence of biliary obstruction (225,226) . The American and British Societies of Gastrointestinal Endoscopy recommend antibiotic prophylaxis for patients submitted to ERC in the presence of biliary obstruction (227,228) .…”
Section: Recurrent Cholangitismentioning
confidence: 99%
“…Vancomycin, metronidazole and minocycline have been evaluated in clinical trials in patients with PSC (60,61). The use of these antibiotics led to a significant reduction in serum ALP, an important surrogate marker in PSC (60,61).…”
Section: Antimicrobials and Pscmentioning
confidence: 99%
“…The use of these antibiotics led to a significant reduction in serum ALP, an important surrogate marker in PSC (60,61). Thus antibiotic therapy in PSC patients seems to be a promising tool in the treatment of PSC.…”
Section: Antimicrobials and Pscmentioning
confidence: 99%